(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Objective The current research sought to evaluate the in vitro activity of Colistin and other agents against multi-drug resistant Pseudomonas aeruginosa isolates. Methodology This in vitro cross-sectional research was carried out October and December 2018 after receiving ethical approval. Pus, wound swabs, blood, tracheal aspirates, and urine samples were regularly collected and obtained from in-patient and out-patient clinics. All samples were given to the department of microbiology at Ziauddin University Hospital's North Nazimabad campus for culture and sensitivity testing. All samples were analyzed in accordance with the CLSI Guidelines 2018. Results Of the 276 Pseudomonas aeruginosa isolates, the majority were from pus (34.2%). MDR Pseudomonas aeruginosa were present in 152 (55%). Female isolates were more resistant than male isolates Antibiotic susceptibility tests revealed that 24% and 20% of P. aeruginosa isolates, respectively, were susceptible to ceftazidime and Imipenem. While Colistin was effective against all P. aeruginosa isolates (p- 0.001). Conclusion Colistin outperformed Imipenem and Ceftazidime against MDR P. Aeruginosa isolates. Colistin has thus emerged as an effective and significant substitute against MDR isolates of P. Aeruginosa, it could be used when no other options are available or the disease is severely detrimental.